Teaching Malaysian culture: the fun way - Paramasivam, Sheela; Adnan, Afni Anida; Kasawi @ Krishnan, Alice Shanti; Ganesan, Asha; Aisya, Nur Fatima (2025)
The teaching of culture as a subject can be interesting and difficult at the same time, especially when it involves understanding another aspect of culture such as religion and customs besides one's own. Assessing students' knowledge and understanding in subjects such as culture is no easy task either. In the digital world today, there are many online assessment tools which can be used to facilitate teaching and learning. One such application is Quizizz, a game-based online quiz. The purpose of this research is to measure the effectiveness of MARC 2.0 (acronym for Malaysian religion and customs), an online Quizizz game to teach culture and gauge students' knowledge and understanding of Malaysian culture. Descriptive questionnaire was used to obtain feedback after students played MARC 2.0, the quizizz game. Results of the survey indicated that students responded positively to the use of MARC 2.0 as a quizizz game to learn and embrace Malaysian culture in a fun and interactive manner and to introduce the culture of Malaysia to any foreign or local students pursuing their studies in Malaysia. The inclusion of attractive visuals, a timer, correct answers as well as scores obtained using MARC 2.0 motivated students to understand, learn and gain insights to the culture of Malaysia in a fun and engaging way. Additionally, MARC 2.0 could be installed in their handphones for convenience. In conclusion, it is important for teachers to consider using fun and entertaining technology-based applications to teach culture to make learning more engaging and meaningful. MARC 2.0 can be further explored and extended to include other aspects of Malaysian culture such as food, festivals, traditional songs, clothes and even taboos to tourists visiting Malaysia in the hope of introducing Malaysia as a land of beauty and diversity.